2015
DOI: 10.1111/1365-2478.12240
|View full text |Cite
|
Sign up to set email alerts
|

Assessing uncertainty in refraction seismic traveltime inversion using a global inversion strategy

Abstract: A B S T R A C TTo analyse and invert refraction seismic travel time data, different approaches and techniques have been proposed. One common approach is to invert first-break travel times employing local optimization approaches. However, these approaches result in a single velocity model, and it is difficult to assess the quality and to quantify uncertainties and non-uniqueness of the found solution. To address these problems, we propose an inversion strategy relying on a global optimization approach known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…In such environments, we expect sharp boundaries and variations along the interfaces due to inundated thermokarst structures (Angelopoulos et al, 2021), pingo-like features, bottom-fast ice versus floating ice regime transitions in winter, or changes in the ratio of coastal erosion vs. degradation rate; i.e., changing from a period of fast thawing and low coastal erosion to a period of fast coastal erosion and slow thawing can result in a heterogeneous structure of the IBPT (e.g., Overduin et al, 2016). Because we expect some of these processes and structures at our field sites, we adopt a strategy based on the sums of arctangent functions because it allows for abrupt and smooth changes along the interfaces (e.g., Roy et al, 2005;Rumpf and Tronicke, 2015). Following Arboleda-Zapata et al (2022), the sums of arctangent functions for a single interface can be written as…”
Section: Two-dimensional Layer-based Model Parameterizationmentioning
confidence: 99%
“…In such environments, we expect sharp boundaries and variations along the interfaces due to inundated thermokarst structures (Angelopoulos et al, 2021), pingo-like features, bottom-fast ice versus floating ice regime transitions in winter, or changes in the ratio of coastal erosion vs. degradation rate; i.e., changing from a period of fast thawing and low coastal erosion to a period of fast coastal erosion and slow thawing can result in a heterogeneous structure of the IBPT (e.g., Overduin et al, 2016). Because we expect some of these processes and structures at our field sites, we adopt a strategy based on the sums of arctangent functions because it allows for abrupt and smooth changes along the interfaces (e.g., Roy et al, 2005;Rumpf and Tronicke, 2015). Following Arboleda-Zapata et al (2022), the sums of arctangent functions for a single interface can be written as…”
Section: Two-dimensional Layer-based Model Parameterizationmentioning
confidence: 99%
“…The uncertainty in geophysical inverse problems was estimated by various stochastic inversion algorithms, such as MCMC (Liu and Stock, 1993;Malinverno and Briggs, 2004;Chen and Dickens, 2009;Gunning et al, 2010;Kwon and Snieder, 2011), SA (Dosso, 2002;Dosso and Nielsen, 2002;Bhattacharya et al, 2003;Roy et al, 2005;Varela et al, 2006), PSO (Fernández-Martínez et al, 2012;Rumpf and Tronicke, 2015), and rjMCMC Reading and Gallagher, 2013;Dadi, 2014;Galetti et al, 2015;Dadi et al, 2015).…”
Section: Uncertainty Estimationmentioning
confidence: 99%
“…These algorithms were originally designed for optimization and are now used to quantify uncertainties (Fernández Martínez et al . ; Tronicke, Paasche and Böniger ; Rumpf and Tronicke ). Luu et al .…”
Section: Introductionmentioning
confidence: 99%
“…These three EAs are becoming more and more popular in the geophysical community because their implementations are straightforward, they require less tuning, they are by nature parallel algorithms and their convergence rates is much higher compared to classical global optimization methods (Angeline 1998;. These algorithms were originally designed for optimization and are now used to quantify uncertainties (Fernández Martínez et al 2012;Tronicke, Paasche and Böniger 2012;Rumpf and Tronicke 2015). Luu et al (2018) showed on a simple real data example that CPSO does sample properly the velocity model parameter space to provide reliable estimates of uncertainty; results were similar to those obtained by MCMC at a much lower computational cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation